Enhanced Stomatal Conductance by a Spontaneous Arabidopsis Tetraploid, Me-0, Results from Increased Stomatal Size and Greater Stomatal Aperture . Issue 3 (11th January 2016) - Monda, Keina; Araki, Hiromitsu; Kuhara, Satoru; Ishigaki, Genki; Akashi, Ryo; Negi, Juntaro; Kojima, Mikiko; Sakakibara, Hitoshi; Takahashi, Sho; Hashimoto-Sugimoto, Mimi; Goto, Nobuharu; Iba, Koh
Abstract : The Arabidopsis tetraploid ecotype, Me-0, overcomes the handicap of stomatal opening that is typical for tetraploid plants and achieves a high stomatal conductance. Abstract: The rate of gas exchange in plants is regulated mainly by stomatal size and density. Generally, higher densities of smaller stomata are advantageous for gas exchange; however, it is unclear what the effect of an extraordinary change in stomatal size might have on a plant's gas-exchange capacity. We investigated the stomatal responses to CO2 concentration changes among 374 Arabidopsis ( Arabidopsis thaliana ) ecotypes and discovered that Mechtshausen (Me-0 ), a natural tetraploid ecotype, has significantly larger stomata and can achieve a high stomatal conductance. We surmised that the cause of the increased stomatal conductance is tetraploidization; however, the stomatal conductance of another tetraploid accession, tetraploid Columbia (Col ), was not as high as that in Me-0 . One difference between these two accessions was the size of their stomatal apertures. Analyses of abscisic acid sensitivity, ion balance, and gene expression profiles suggested that physiological or genetic factors restrict the stomatal opening in tetraploid Col but not in Me-0 . Our results show that Me-0 overcomes the handicap of stomatal opening that is typical for tetraploids and achieves higher stomatal conductance compared with the closely related tetraploid Col on account of larger stomatal apertures. This study provides evidence for whether larger stomatal size in tetraploids of higher plants can improve stomatal conductance.